The natural feed resources for ruminant animals in Nigeria - Umunna, N.N.; Iji, P.A. (Nigeria Ministry of Agriculture and Water Resources, 1993)
The paper assesses the feed resources available for ruminant production in Nigeria. The paper highlights ruminant animal contribution and feed situation and describes forage resoruces of the Savanna. Crop residue yield and utilization anare discussed and low and high cost input improvement scheme are summarised.